TAWHID AND ISLAMIC PHILOSOPHY : EXPLORING THE UNITY OF GOD IN ISLAMIC LOGIC - Torres Fernández, Antonio (LTN NU Sulawesi Tengah, 2023)
This paper aims to delve into the realm of Islamic logic by conducting a comprehensive analysis of epistemology and reasoning regarding the concept of tawhid within the context of Islamic thought. Drawing from a wide range of primary and secondary sources, this study explores the distinctive features and foundations of Islamic logic, highlighting tawhid and its significance in understanding knowledge acquisition and rational inquiry in the Islamic tradition. It explores the contributions of prominent Muslim scholars, such as Al-Kindi, Al-Farabi, Ibn Sina, and Ibn Rushd, who made significant advancements in the field of logic. And it was found that tawhid serves as a foundational principle in Islamic logic, shaping the understanding of knowledge acquisition and rational inquiry within the Islamic tradition. The contributions of these scholars exemplify the compatibility between reason and revelation, providing a comprehensive framework for logical reasoning grounded in the principles of tawhid. Their ideas continue to inspire and shape contemporary discussions on Islamic logic, reflecting the enduring legacy of their intellectual contributions.